Correlations of social isolation and anxiety and depression symptoms among patients with breast cancer of Heilongjiang province in China: The mediating role of social support - Bingshuo Liu; Xinyu Wu; Lei Shi; Han Li; Di Wu; Xin Lai; Yuyan Li; Yue Yang; Danni Li (Wiley, 2021)
Abstract Objectives To explore the correlations among social isolation and symptoms of anxiety and depression among patients with breast cancer in China and to further verify the mediating role of social support in social isolation and symptoms of depression or anxiety. Design A cross‐sectional survey. Settings The cluster sampling method was conducted for 456 female inpatients diagnosed with breast cancer at the Tumor Hospital Affiliated of Harbin Medical University from April 2019-September 2019. Methods Pearson correlation analysis was used for identifying correlations among all the variables. Mediation effect analysis was used to examine the role of social support in social isolation and symptoms of depression or anxiety. Results The results showed a prevalence of 73.26% and 70.44% for anxiety and depression symptoms in patients with breast cancer, respectively. Anxiety was significantly negatively correlated with social support (r = −.334, p < .01) and significantly positively correlated with social isolation (r = .369, p < .01). Similarly, depression was significantly negatively correlated with social support (r = −.289, p < .01) and significantly positively correlated with social isolation (r = .466, p < .01). Social support played a mediating role in social isolation and f symptoms of anxiety or depression among these patients. Conclusions Social isolation was positively correlated with symptoms of anxiety and depression in patients with breast cancer, respectively. Social support for patients with breast cancer has a mediating effect on the patients' social isolation and symptoms of anxiety and depression. Therefore, the support of family, friends, hospitals, and organizations plays a positive role in reducing social isolation as well as symptoms of depression and anxiety in these patients.